Symptomatic Supraventricular Tachycardia Resistant to Adenosine Therapy in a Patient with Chronic Theophylline Use. (28th March 2021) - Hosseini, Seyedeh Maryam; Ajmal, Muhammad; Shetty, Ranjith
Abstract : Theophylline is a potent adenosine receptor antagonist with indirect adrenergic effects that can lead to arrhythmias and metabolic abnormalities such as hypokalemia. Therapeutic toxicity cases have declined over the years mainly due to decreased recommended therapeutic doses and overall decreased usage of this medication due to newer available COPD treatment options. We present a clinical case of symptomatic supraventricular tachycardia resistant to adenosine therapy in a patient with theophylline use. This case highlights the importance of comprehensive medication review in acute settings to aid in identifying the underlying etiologies and initiating prompt treatments. It also signifies the importance of reviewing chronic medications in each outpatient visits to ensure continued indication for their use and be able to change them to newer agents per guidelines whenever possible.